2013
DOI: 10.2106/jbjs.l.00222
|View full text |Cite
|
Sign up to set email alerts
|

Human Growth Hormone May Be Detrimental When Used to Accelerate Recovery from Acute Tendon-Bone Interface Injuries

Abstract: In this rat model of acute tendon-bone injury repair, daily subcutaneous postoperative human growth hormone treatment for fourteen days failed to demonstrate a significant difference in any biomechanical parameter compared with placebo. Furthermore, subcutaneous administration of 5 mg/kg of human growth hormone twice daily from seven days preoperatively until twenty-eight days postoperatively demonstrated lower loads to ultimate failure and a higher risk of bone fracture failure compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The supraspinatus tendon was fixed between sandpaper using cyanoacrylate glue and held vertically in a custom clamp. Specimens were preconditioned from 0 to 5% strain at a rate of 1% strain/sec for five cycles, followed by a displacement ramp to failure at a rate of 1% strain/sec …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The supraspinatus tendon was fixed between sandpaper using cyanoacrylate glue and held vertically in a custom clamp. Specimens were preconditioned from 0 to 5% strain at a rate of 1% strain/sec for five cycles, followed by a displacement ramp to failure at a rate of 1% strain/sec …”
Section: Methodsmentioning
confidence: 99%
“…Specimens were preconditioned from 0 to 5% strain at a rate of 1% strain/sec for five cycles, followed by a displacement ramp to failure at a rate of 1% strain/sec. [21][22][23] Micro-CT Analysis Eight weeks after repair surgery (Surgery 2), eight rats per group were sacrificed and the bilateral humeral bones with SSp muscles were harvested. Specimens were fixed in 10% formalin for 48 h at room temperature.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…The test protocol was similar to that used in previous studies . Specimens were preloaded to 0.2 N and preconditioned for five cycles to 5% strain at a rate of 1% strain/s.…”
Section: Methodsmentioning
confidence: 99%
“…29,30 While these findings allude to potential for GH use in direct tendon healing, in vivo studies by Baumgarten et al and Oh et al have respectively shown detrimental effects on rats and insignificant effects on humans with RCRs. 27,28 Baumgarten et al carried out a two cohort treatment study on rats who underwent repair of acute RCTs. 27 The first cohort (n= 72) received postoperative treatment of placebo or subcutaneous GH at doses ranging between 0.1 to 10 mg/kg/day while the second cohort (n= 24) underwent either placebo or seven days preoperatively and twenty eight days postoperatively of 5 ml/kg of GH.…”
Section: Hormones: Estrogenmentioning
confidence: 99%